Monitoring the availability of healthy and unhealthy foods and non‐alcoholic beverages in community and consumer retail food environments globally. (17th September 2013) - Ni Mhurchu, C.; Vandevijvere, S.; Waterlander, W.; Thornton, L. E.; Kelly, B.; Cameron, A. J.; Snowdon, W.; Swinburn, B.; ,
Summary: Retail food environments are increasingly considered influential in determining dietary behaviours and health outcomes. We reviewed the available evidence on associations between community (type, availability and accessibility of food outlets) and consumer (product availability, prices, promotions and nutritional quality within stores) food environments and dietary outcomes in order to develop an evidence‐based framework for monitoring the availability of healthy and unhealthy foods and non‐alcoholic beverages in retail food environments. Current evidence is suggestive of an association between community and consumer food environments and dietary outcomes; however, substantial heterogeneity in study designs, methods and measurement tools makes it difficult to draw firm conclusions. The use of standardized tools to monitor local food environments within and across countries may help to validate this relationship. We propose a step‐wise framework to monitor and benchmark community and consumer retail food environments that can be used to assess density of healthy and unhealthy food outlets; measure proximity of healthy and unhealthy food outlets to homes/schools; evaluate availability of healthy and unhealthy foods in‐store; compare food environments over time and between regions and countries; evaluate compliance with local policies, guidelines or voluntary codes of practice; and determine the impact of changes to retail food environments on health outcomes, such as obesity.